High temperature, transparent, superhydrophobic Teflon AF-2400/Indium tin oxide nanocomposite thin films. (15th February 2019) - Alawajji, Raad A; Kannarpady, Ganesh K; Nima, Zeid A; Kelly, Nigel; Watanabe, Fumiya; Biris, Alexandru S
Abstract: The outstanding properties of Teflon AF-2400—chemical, optical, etc—inspired us to make modifications to enhance its hydrophobicity. We prepared an AF-2400/indium tin oxide (ITO) nanocomposite by a spin coating technique at room temperature, using the AF-2400 polymer as the matrix and ITO nanoparticles as the filler. Different ITON concentrations ranging from 3 to 30 mg ml −1 were prepared to study the effect of nanoparticle loading on the films' properties and superhydrophobicity. The effect of spin speed and annealing temperature was also studied. Atomic force microscopy, x-ray photoelectron spectroscopy, and UV–vis analysis were employed to characterize the prepared films. The results indicated that the film's low surface energy and nano/micro-features made it superhydrophobic. Increasing the ITON concentration to 15 mg ml −1 improved the superhydrophobicity of the composite film by increasing the surface roughness. The coating showed superhydrophobic behavior with a static contact angle (SCA) around 152° and contact angle hysteresis less than 2°. The nanocomposite films also exhibited excellent thermal stability, sustaining temperatures as high as 240 °C without losing their superhydrophobic behavior. Three models, Wenzel, Cassie–Baxter, and Shuttleworth–Bailey, were used to predict the SCA. The results confirmed that the latter model gave the best prediction. In addition to superhydrophobicity, the AF-2400/ITON films coated on a glass substrate showed very high transparency—around 95% in the visible and infrared ranges. An effective medium theory, the Bergman representation, was used to simulate the transmittance of the AF-2400/ITON nanocomposites. The measured and simulated transmittance values were in good agreement in the visible range. Based on our results, this coating may be highly useful for many practical applications, including solar cell coatings, chemical resistance protective coatings, and more.